Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening - Rafika Rachmaniah (Jurnal Manajerial, 2022)
Background – Changes from the 4.0 era had an impact on human resource management so that this caused problems. This makes every organization must face challenges by conducting experiments and improving management in the field of human resource management. Purpose – The purpose of this study was to analyze the significance of the effect of work discipline and work motivation on employee performance. This study also investigates the role of the connecting variabel of job satisfaction in improving employee performance. Design / methodology / approach – The purpose of this study was to analyze the significance of the effect of work discipline and work motivation on employee performance. This study also investigates the role of the connecting variabel of job satisfaction in improving employee performance. Findings – The results showed that work discipline and work motivation had a significant effect on employee satisfaction. Employee satisfaction has a significant effect on employee performance. Indirectly, work discipline and work motivation also have a significant effect on employee performance. Each variabel obtained by the path coefficient shows an indirect effect. Conclusion - Concluded that work discipline, work motivation, and employee job satisfaction have an important role in employee performance. Research implication – The results of this study are expected to be input for Bank BRI Manukan Surabaya Branch Office, especially knowing the effect of work motivation and work discipline on employee performance with job satisfaction as an intervening variabel, can be used as learning material and application of knowledge in the field of management, especially in the field of human resource management. and can be an additional reference for further research and as a consideration for organizations facing similar problems. Limitations – Limitations in this study are independent variabels that only use 2 variabels in this study, namely work discipline and work motivation and the number of research respondents totaling 100 respondents.